Shared Metacognition, Collaboration and the Community of Inquiry Framework in Action - Sevnarayan, Kershnee; Vaughan, Norman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study explored the application of the Community of Inquiry (CoI) framework in a large enrollment online course, which focuses specifically on collaborative learning and student engagement. The CoI framework, which comprises social, cognitive, and teaching presence, provides a theoretical foundation for understanding how students construct personal meaning and confirm mutual understanding. While metacognition has been an important factor in learning, its role in collaborative online learning environments is poorly understood. This mixed-methods study investigates the impact of shared metacognition on collaboration in a large-enrollment online Academic Writing course at an open distance learning university in South Africa. The study employed the Shared Metacognition survey, which was developed from the CoI framework, to collect data from 1200 students at three stages: pre-module, midpoint, and post-module. Statistical analysis and qualitative content analysis were used to examine self-regulation and co-regulation dimensions of metacognition. The findings highlight the significance of teaching presence in predicting student success and satisfaction. Shared metacognition emerged as a significant factor in developing collaborative learning environments. Students’ awareness of their thinking and learning processes improved through critical discourse and peer interaction. This research contributes to the understanding of collaborative learning in large courses and emphasises the importance of metacognitive awareness and shared regulatory functions. The study has significant implications for lecturers, practitioners, and instructional designers in large modules who seek to enhance collaborative learning experiences in online education.